Netralitas Netralitas Perangkat Desa Dalam Pilkada Serentak Tahun 2024 Di Kabupaten Bantul - Bintang Ashara Bela; Dian Eka Rahmawati (Universitas Muhammadiyah Ponorogo, 2026)
The neutrality of village apparatus is an imperative obligation that must be upheld without compromise. This study aims to analyze the neutrality of village apparatus during the simultaneous regional elections (Pilkada) in 2024 in Bantul Regency. A qualitative approach was employed, with data collected through interviews and documentation studies. The findings reveal several violations committed by village officials that contradict the principle of neutrality. The causes of this lack of neutrality are influenced by several factors, including cultural influences, political ambition, kinship or familial ties, and local political pressures. In Javanese culture, the concept of